Acinetobacter albensis sp. nov., isolated from natural soil and water ecosystems - Krizova, Lenka; Maixnerova, Martina; Sedo, Ondrej; Nemec, Alexandr (International journal of systematic and evolutionary microbiology, 2015)
We have studied the taxonomic position of a phenetically unique group of eight strains of the genus Acinetobacter which were isolated from soil and water samples collected in protected landscape areas in the Czech Republic. Each of the comparative sequence analyses of the 16S rRNA, gyrB and rpoB genes showed that the eight strains formed a cohesive and tight cluster (intracluster sequence identities of ≥ 99.9 %, ≥ 98.5 % and ≥ 97.7 %, respectively), which was clearly separated from all hitherto known species of the genus Acinetobacter ( ≤ 98.6 %, ≤ 84.5 % and ≤ 89.3 %, respectively). Congruent with these findings were the results of comparative sequence analysis of three additional housekeeping genes (gltA, pyrG and recA). This genotypic distinctness was mirrored by the uniqueness of the combination of a number of independent phenotypic markers including the whole-cell spectra produced by matrix-assisted laser desorption ionization time-of-flight (MALDI-ToF) MS and physiological and metabolic features. The most useful phenotypic features to differentiate the eight strains from all known species of the genus Acinetobacter were the ability to assimilate tricarballylate and the inability to grow at 35 °C or to assimilate ethanol or l-histidine. We conclude that the eight strains represent a novel environmental species for which the name Acinetobacter albensis sp. nov. is proposed. The type strain is ANC 4874T ( = CCUG 67281T = CCM 8611T).